(untitled) (International relations and international law Journal, 2016)
Water resources in Central Asia are strategically important, because they have a great influence on economic activity and welfare of the population in the region. All large rivers of the CA are transboundary, therefore any changes in water use affect interests of the states incommon water ecosystem. After collapse of the USSR, the countries of the region faced a problem of reforming the structure of international waterways management as previous mode of water division and barter deliveries was interrupted. Today the legal base on the regional transboundary rivers includes not only the regional agreements, and also documents on a bilateral and tripartite basis. Nevertheless there are contradictions in countries’water politics, and the agreements regulating the interstate relations in a water management complex are insufficiently systematized and coordinated. Author consider the development of water relations among states of the region, and also carries out the analysis of the main agreements.